2021
DOI: 10.1039/d1ma00523e
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stable high-contrast iridescent structural colours from silica colloidal crystals doped with monodisperse spherical black carbon particles

Abstract: Monodisperse black carbon nanoparticles (average diameter: 272 and 511 nm) are prepared by carbonization of monodisperse spherical π-conjugated polymer particles. Meanwhile, silica nanoparticles of different sizes are prepared by conventional...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…Carbon-based materials, such as CB and melanin, are oxidized at high temperatures in air and decompose into carbon dioxide (CO 2 ). There have been few reports on the heat resistance of colloidal-array-type structurally colored materials using carbon-based black additives; only heat resistances up to 350 and 450 °C have been reported. , Fe 3 O 4 is oxidized to Fe 2 O 3 , and its color is converted from black to red in air at 300 °C . The low heat resistances of these black additives thus prevent a wide variety of applications for structurally colored materials, such as ceramic glazes.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-based materials, such as CB and melanin, are oxidized at high temperatures in air and decompose into carbon dioxide (CO 2 ). There have been few reports on the heat resistance of colloidal-array-type structurally colored materials using carbon-based black additives; only heat resistances up to 350 and 450 °C have been reported. , Fe 3 O 4 is oxidized to Fe 2 O 3 , and its color is converted from black to red in air at 300 °C . The low heat resistances of these black additives thus prevent a wide variety of applications for structurally colored materials, such as ceramic glazes.…”
Section: Introductionmentioning
confidence: 99%
“…However, this limits the structures' temperature stability under ambient conditions (air) to ∼350 °C due to carbon burnout. 26 Meanwhile, preceramic polymers not only present outstanding shaping abilities, but the later conversion to ceramic glass results in excellent thermal stability, making them ideal for use in harsh environments. 16,27 In this study, we investigated an approach to produce ceramic-based PhG having preceramic precursors as starting material, which enabled the printing of ceramic structural color that demonstrates high color saturation even under diffuse illumination and white surroundings.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In previously reported studies, carbon is usually added as an absorber between ceramic particles to maintain the saturation of the structural color in front of white backgrounds, too. However, this limits the structures’ temperature stability under ambient conditions (air) to ∼350 °C due to carbon burn-out . Meanwhile, preceramic polymers not only present outstanding shaping abilities, but the later conversion to ceramic glass results in excellent thermal stability, making them ideal for use in harsh environments. , …”
Section: Introductionmentioning
confidence: 99%
“…Inspired by these elegant examples in nature, many studies have explored light absorption materials to prepare photonic materials with enhanced brightness and biomimetic metallic effects. In the cases of CNC-based chiral photonic films, Droguet et al recently achieved certain metallic effects in the coloration of partially carbonized CNC films by heating the neat films at very high temperature . However, further carbonation leaded to black materials without any colors and fragmentation of the CNC films.…”
Section: Introductionmentioning
confidence: 99%
“…However, further carbonation leaded to black materials without any colors and fragmentation of the CNC films. Instead of such a specific method, incorporation of light absorption materials into photonic materials is a more general strategy. By doping thermally reduced graphene (TRG) into CNC films, Nan et al imparted certain metallic effects into their hybrid CNC/TRG films . Wang et al recently reported cellulose films with vivid colors by preparing the pristine CNC-based photonic films at first and then infiltrated the films with the light adsorption materials of polydopamine (PDA) .…”
Section: Introductionmentioning
confidence: 99%